2015
DOI: 10.1186/s12911-016-0245-z
|View full text |Cite
|
Sign up to set email alerts
|

User perspectives on an electronic decision-support tool performing comprehensive medication reviews - a focus group study with physicians and nurses

Abstract: BackgroundAlthough a number of studies have evaluated the effectiveness of computerized decision-support systems (CDSS), there is lack of data on user perspectives, barriers, and facilitators to the implementation of CDSSs in real-life surroundings. The aim of this study was to assess individually perceived barriers, facilitators and ideas influencing the CDSS implementation and usability.MethodsIn this qualitative study, five focus groups were carried out with physicians and nurses separately at the Tampere C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 23 publications
(29 reference statements)
0
38
1
1
Order By: Relevance
“…Although the RNs did not report any great effects, many wanted to continue using the CDSS, indicating that they saw potential benefits in it. The use of a CDSS in drug monitoring has previously been described to promote team-collaboration and the acquisition of knowledge (Johansson-Pajala et al, 2017, Koskela et al, 2016, findings that were not confirmed here.…”
Section: Rns' Observations and Views (I Ii)contrasting
confidence: 74%
See 1 more Smart Citation
“…Although the RNs did not report any great effects, many wanted to continue using the CDSS, indicating that they saw potential benefits in it. The use of a CDSS in drug monitoring has previously been described to promote team-collaboration and the acquisition of knowledge (Johansson-Pajala et al, 2017, Koskela et al, 2016, findings that were not confirmed here.…”
Section: Rns' Observations and Views (I Ii)contrasting
confidence: 74%
“…There are also few studies reporting on the use of CDSSs in medication reviews. Not only could a CDSS be supportive for prescribers and clinical pharmacists, but also for the RNs who screen for 4 DRPs (Bernstein et al, 2014;Dilles et al, 2013;Koskela et al, 2016). The provision of high-quality, safe care is highly dependent on the RNs' ability to access and integrate relevant information into their clinical decision-making (Fossum et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a number of participants highlighted that their motivation for identifying and reporting resident goals and concerns was their belief in their duty to advocate for the resident. Previous studies highlight the perceptions of health‐care providers regarding roles and responsibilities as a factor impacting on the use of CCDSS . This qualitative study illustrates that the motivation of staff to undertake the behaviour and deferring roles to others is an important factor as well.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies highlight the perceptions of health-care providers regarding roles and responsibilities as a factor impacting on the use of CCDSS. 21,22 This qualitative study illustrates that the motivation of staff to undertake the behaviour and deferring roles to others is an important factor as well.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, once a CDS tool is developed, the use of "usability sessions" with providers that are likely to be working with the CDS tool has been shown maximize the chances of achieving the clinical behavior for which the tool was designed. 29,30 As outlined by Miller and colleagues 25,26,31 in the International Journal of Medical Informatics, there are no real design or functional requirements for effective CDS, and this leaves many CDS tools limited by poor usability once deployed. One of their key takeaway points was to be sure to include a minimum of three analyzers to test usability of the tool before implementation.…”
Section: Discussionmentioning
confidence: 99%